2016
DOI: 10.1515/hc-2016-0039
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimidinethione as a building block in heterocyclic synthesis: synthesis of pyrano[2,3-d]pyrimidine, chromeno[2,3-d]pyrimidine, pyrido[3′,2′:5,6]pyrano[2,3-b]pyridine, and pyrimido[5′,4′:5,6]pyrano[2,3-d]pyrimidine derivatives

Abstract: New heterocyclic compounds with expected biological activity have been prepared by reactions of 6-phenyl-2-thioxo-2,3-dihydropyrimidine-4(5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Abdel-Reheim et al 138 have reported the synthesis of dihydropyrimidinone 67 from the reaction of thiourea with ethyl benzoyl acetate and applied this compound in the multi-step synthesis of bicyclic pyranopyrimidines by reactions with arylidenes, or by the multicomponent reaction with formaldehyde, and malononitrile. Also, the reactivity of pyranopyrimidine 69b towards diverse reagents e.g.…”
Section: Synthetic Applicationsmentioning
confidence: 99%
“…Abdel-Reheim et al 138 have reported the synthesis of dihydropyrimidinone 67 from the reaction of thiourea with ethyl benzoyl acetate and applied this compound in the multi-step synthesis of bicyclic pyranopyrimidines by reactions with arylidenes, or by the multicomponent reaction with formaldehyde, and malononitrile. Also, the reactivity of pyranopyrimidine 69b towards diverse reagents e.g.…”
Section: Synthetic Applicationsmentioning
confidence: 99%
“…Carbon–heteroatom and carbon–carbon bond-forming reactions lie at the heart of organic synthesis. Multicomponent reactions (MCRs) have been recognized as valuable tools in modern organic synthesis for the drug discovery process and the total synthesis of natural products. MCRs can provide access to a library of complex structures in a straightforward manner, and diversity can be achieved for building up compound libraries by simply varying each component. , Over the past four decades, there has been a huge development in three- and four-component reactions, and great endeavor continues to be made to expand new MCRs. …”
Section: Introductionmentioning
confidence: 99%